PEMANFAATAN MEDIA KOMIK UNTUK MENINGKATKAN HASIL BELAJAR MENULIS NARASI PADA SISWA KELAS IV SDN JABUNG 2 - Vivi Rulviana (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2020)
The research objective is to find out the improvement in the ability to write narration with comic media in fourth grade students of SDN Jabung 2.The research method used is classroom action research. The research subjects are four students out of 15 students. The implementation phase is planning, action, observation, reflection phase. Data collection is done by observation, interview and documentation.The results showed that the first cycle had not been completed with OM (68.75), DJ (68.75), RD (68.75) and SN (87.5) grades, so that improvements were made in the second cycle where all four students received OM values (81.25), DJ (68.75), RD (75) and SN (81.25). The use of comics as a medium for learning to write narration is an effort to improve student learning outcomes.